Liberation Technology: Mobile Phones and Political Mobilization in Africa - Manacorda, Marco; Tesei, Andrea (Econometrica, 2020)
Can digital information and communication technology foster mass political mobilization? We use a novel georeferenced data set for the entire African continent between 1998 and 2012 on the coverage of mobile phone signal together with georeferenced data from multiple sources on the occurrence of protests and on individual participation in protests to bring this argument to empirical scrutiny. We find that while mobile phones are instrumental to mass mobilization, this only happens during economic downturns, when reasons for grievance emerge and the cost of participation falls. The results are in line with insights from a network model with imperfect information and strategic complementarities in protest occurrence. Mobile phones make individuals more responsive to both changes in economic conditions—a mechanism that we ascribe to enhanced information —and to their neighbors' participation—a mechanism that we ascribe to enhanced coordination .